(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Background: In worldwide, 20-25% of the population have the Metabolic Syndrome (MetS). The highest prevalence rate reported in South Asia of MetS in the Punjabi community in India by Adult Treatment Panel III criteria. The metabolic syndrome (MetS) is a major and escalating public-health and clinical challenge worldwide in the wake of rapid urbanization, surplus energy intake, increasing obesity, and sedentary life habits. Nowadays, the use of Complementary and Alternative Medicine (CAM) is increasing rapidly due to the inadequate solution for the newly developed health issues. Method: In this study, the International Diabetic Federation (IDF) criteria were used as a standard tool for comparison. A total of 9 sources (4 Siddha classical textbooks, e-data such as pub-med, Google scholar, AYUSH research portal, NAMSTP) were searched to identify the appropriate analog for MetS. Results: 13 Terms related to MetS were identified from the 4 Siddha classical literature, whereas the e-data did not provide any term related to MetS. In those 13 terms, 3 terms which were closely relevant to MetS signs and symptoms were Aiya Migu Kunam, Paci Aiya Noi, and Megam. As a final point, this paper identified the Siddha analog for MetS as Aiyamigukunam. Conclusion: This paper ended up with analog to MetS as Aiyamigukunam and made a comparison with the standard IDF criteria for MetS.